Analysis of genotyping for predicting liver injury marker, procollagen III in persons at risk of non‐alcoholic fatty liver disease. (25th March 2018) - Grove, Jane I.; Thiagarajan, Prarthana; Astbury, Stuart; Harris, Rebecca; Delahooke, Toby; Guha, I. Neil; Aithal, Guruprasad P.
Abstract: Background & Aims: Chronic liver disease presents a major global public health challenge. Stratification of asymptomatic, at‐risk patients in primary care using non‐invasive methods has the potential to address this by identifying those likely to progress. We, therefore, evaluated variant alleles at loci associated with non‐alcoholic fatty liver disease as genetic determinants of substantial liver injury in patients with disease risk factors. Methods: Levels of serum procollagen III (PIIINP), an established fibrosis and steatohepatitis marker, were determined in 467 people who had type 2 diabetes and/or BMI > 27.3 (identified from registration with general practitioners) in this observational cross‐sectional study. Patients were genotyped for characterised risk alleles in PNPLA3 (rs738409), GCKR (rs1260326) and TM6SF2 (rs58542926) and associations with PIIINP assessed. Results: The risk alleles in PNPLA3, GCKR or TM6SF2 were not found to be individually associated with the presence of a disease risk factor and were not significantly more common in patients with raised serum PIIINP. The prevalence of possession of both PNPLA3 and GCKR variant alleles combined was significantly higher in at‐risk patients with clinically significant liver disease indicated by serum PIIINP above 11 ng/mL ( P = .014). Conclusions: Genotyping, therefore, has limited value for predicting severe liver disease in at‐risk individuals identified in a community setting.